Small signal stability in low-renewable power systems: A 138 kV Santo Domingo case study - Ángel José Sánchez-Sánchez; Miguel Aybar-Mejía; Víctor Ernesto Peralta-Maxwell; Ángel Dagoberto Germán-Encarnación; Eduardo De León-Concepción; Deyslen Mariano-Hernández (Revista Facultad de Ingeniería Universidad de Antioquia)
Small signal stability in electrical systems refers to the ability of the system to maintain stable operation in the face of low-amplitude disturbances, such as fluctuations in electrical demand or the off and on switching of generators. This type of analysis is essential because it provides insight into how the system responds to minor disturbances, such as variations in generation or unplanned load. Significant disturbances can induce unstable conditions with potentially serious consequences, such as widespread power outages. Advanced mathematical techniques address these issues, such as the Fourier transform and the Prony method. In this study, a method was developed using MATLAB, and flow runs were performed in Digsilent software to analyze the oscillations of small signals in a 138 kV substation with low penetration of renewable energy. This research is relevant because it allows us to assess the impact of small disturbances in the electricity system during the transition toward greater integration of renewable technologies. The goal is to improve the efficiency and safety of electrical infrastructure in the Dominican Republic, ensuring a more reliable and stable energy supply for residents and businesses. The analysis shows that the current system can absorb anomalies of small signals due to the low penetration of renewables. In addition, the tool developed allows the evaluation of scenarios with greater penetration of renewable energy, providing a solid basis for implementing preventive or corrective measures.